Efektivitas Pemberian Ramuan Kunyit Asam dan AIR Rebusan Jahe Merah Terhadap Penurunan Nyeri Disminorea Primer Pada Remaja - Agustine, Pebry Prila; Apriyani, Magdalena Tri Putri; Valianda, Feni (Jurnal Ilmu Kebidanan, 2024)
Background: Menstruation is bleeding from the uterus that occurs periodically and cyclically. Dysmenorrhea is pain during menstruation, usually characterized by a sinking feeling centered in the lower abdomen. In Banten province, the incidence of young women experiencing dysmenorrhea is around 26%. South Tangerang City Health Service, in the South Tangerang City Community Health Center in 2011, the total number of visits by dysmenorrhea patients was 237 cases, in 2012 it increased by 435 cases, and in 2013 there were 424 cases. This study aims to determine the comparative effectiveness of administering a concoction of tamarind turmeric and red ginger decoction to reduce dysmenorrhoea pain in adolescents. Methods: ; The method used in this research is qualitative with a case study approach. Results: Based on the research results, it was found that the intervention of giving tamarind turmeric concoction had an effect on reducing dysmenorrhoea pain and the intervention of giving red ginger decoction had an effect on reducing dysmenorrhoea pain in adolescents. It was found that there was a difference in the effect of providing intervention, namely that the turmeric tamarind concoction intervention showed more effective results more quickly in reducing menstrual pain experienced by young women with dysmenorrhoea. Conclusion The comparison shows that both have the same effectiveness, but giving a turmeric tamarind concoction to teenagers has a faster effect compared to giving red ginger decoction.